The Stylistics of Al-Mustawā Ad-Dalālī in the Verses of Monotheism in Surah Al-Mulk - Rabi’ah Al-Adawiyah; Asep Sopian; Nalahuddin Saleh (Universitas Cokroaminoto Palopo, 2025)
This study aims to reveal how the semantic level in the verses of monotheism in Surah Al-Mulk is employed to reinforce the impression of monotheism. The focus of the study is directed toward the selection of diction, polysemy, synonymy, and antonymy that carry profound meanings related to this monotheistic impression. This research adopts a qualitative method with a content analysis approach applied to the verses of Surah Al-Mulk, using tafsir sources from Tafsīr Al-Miṣbāḥ, Al-Marāghī, Al-Munīr, Al-Kashshāf, Ibn Kathīr, Al-Muyassar, and Tafsīr Al-Qurṭubī. The analysis is conducted by selecting the tafsir that most closely aligns with the meaning of the word under study, ensuring that the explanations remain focused and consistent. The findings indicate that the choice of words in Surah Al-Mulk is not coincidental but intentional and strategic in affirming the power and oneness of Allah, as seen in the use of the words يَد (power), أَفْئِدَةٌ (heart), and the antonym pair الْمَوْت – الْحَيَاة (death–life), which strengthen the monotheistic impression. These findings affirm that the rhetorical power of the Qur’anic language at the semantic level can convey the impression of monotheism in a profound and effective manner, while also contributing to the study of Qur’anic stylistics.